2021
DOI: 10.47191/ijcsrr/v4-i7-23
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Situational Leadership, Work Environment, Competence, and Motivation on Employee Job Satisfaction at the National Library of Indonesia

Abstract: This study aims to determine the effect of situational leadership, work environment, competence, and motivation on employee satisfaction at the National Library. The research population is the National Library employees who work in the Deputy for Library Material Development and Information Services, with a total sample of 195 people. The design of this research is quantitative research with a data analysis method using multiple linear regression. The results of the study state that situational leadership has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…In relation to employee affection (H4), the results of this research indicated that it does not have a significant influence on user satisfaction, which is different from previous studies [4], [42], [43], [44], [45]. These findings could be due to the fact that, while friendly and empathetic treatment by staff is important [46], it is not a major factor in determining users' satisfaction with the virtual library service.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…In relation to employee affection (H4), the results of this research indicated that it does not have a significant influence on user satisfaction, which is different from previous studies [4], [42], [43], [44], [45]. These findings could be due to the fact that, while friendly and empathetic treatment by staff is important [46], it is not a major factor in determining users' satisfaction with the virtual library service.…”
Section: Discussioncontrasting
confidence: 89%
“…• H1: The quality of the system influences satisfaction • H2: The quality of information influences satisfaction • H3: The quality of services influences satisfaction The ability and responsiveness of an employee has an impact on user satisfaction [42]. Therefore, the competencies and behaviour of library staff are relevant to user satisfaction [42], [43], so when employees show appreciation, care and kindness towards users, it can improve the service experience and increase user satisfaction [4], [44]. The work environment, including factors such as situational leadership and motivation, can also influence employee job satisfaction, which in turn affects library user satisfaction, because if employees are happy in their work environment, they are more likely to be committed and motivated in their roles, offering better customer service and a more positive interaction with library users [44].…”
Section: Satisfaction and Loyalty In Librariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaders who practice innovations, their leadership attitudes and behaviors are based on developing knowledge, and intellectually can translate them into productive performance. Intellectual stimulation means that leaders can provide work or main tasks for each individual according to their abilities and encourage innovation and creativity by questioning the assumptions used and supporting problem-solving efforts, [6].…”
Section: Individual Considerationsmentioning
confidence: 99%